The consolidated system of electric car lighting - Grabendike, Frank W. (My University, 1907)
Introduction: Electric Car Lighting has today passed beyond the experimental stage and has established for itself, an important and recognized place in the realm of electrical engineering. The subject of car lighting is one with which every energetic railway manager has to deal and the electrical lighting of railway cars is demanding the attention of most of the railroads throughout the world. The success of an invention depends upon two things, first upon its capacity for accomplishing the results for which it was designed; and secondly,the demand created for the invention, when it is placed upon the market or put into general service. Electric car lighting fulfills both of these conditions and its success today is proven without a doubt. Electricity is universally admitted to be the best means of supplying light providing it can be produced and regulated successfully. Many systems of regulation and control have been devised and are now in operation on the trains of various railway companies.The success of electric lighted trains may also be attributed to the fact, that the travelling public demand the best service from our railroad companies. The public is no longer content to ride in cars where the furniture is covered with grease and dirt from old oil lamps, nor does any one enjoy inhaling the obnoxious gases, so common to cars lighted with gas, when competitors are offering for the same rate, elegantly furnished cars, free from dirt, grease or odor, and brilliantly and evenly lighted with the modern incadescent lamp. The electric lighting of cars is accomplished by means of many different systems. Each system must have a source of power, a means of regulating and controlling this power and lastly an efficient means of distribution. In the last few years, marked improvements have been made in various systems of car lighting over some of the earlier types.
Citation: Grabendike, Frank W. The consolidated system of electric car lighting. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Electric Cars; Lighting; Technological Implementation; Theses